Does Ondansetron Modify Sympathectomy Due to Subarachnoid Anesthesia?: Meta-Analysis, Meta-Regression, and Trial Sequential Analysis. Issue 1 (March 2017) - Terkawi, Abdullah S.; Mavridis, Dimitris; Flood, Pamela; Wetterslev, Jørn; Terkawi, Rayan S.; Bin Abdulhak, Aref A.; Nunemaker, Megan S.; Tiouririne, Mohamed
Abstract : ( Anesthesiology. 2016;124:846–869) Subarachnoid anesthesia, used in abdominal and lower extremity surgeries, has side effects including hypotension and bradycardia. Ondansetron, a potent 5-HT3 receptor antagonist, was found to prevent the consequences of sympathectomy in earlier studies but these were underpowered and presented variable results. This study evaluated the existing data on the efficacy of ondansetron in preventing hypotension and bradycardia due to subarachnoid anesthesia. A literature search was performed from the MEDLINE databases using PubMed, Cochrane Library, and Web of Science. The primary outcomes were the incidence of hypotension and bradycardia after subarachnoid anesthesia, and secondary outcomes were vasopressor (phenylephrine and ephedrine) consumption. Random-effects models were used to determine the ondansetron effect a priori. Data were analyzed by standard meta-analysis and recently developed statistical techniques such as small trial bias assessments, selection models, trial sequential analyses (TSAs) to estimate adjusted confidence intervals (CIs), and the Grading of Recommendations on Assessment, Development, and Evaluation system.